Management of Covid-19 Patients with Diabetes Mellitus - Stefani Agustin Parapasan; Rossalia Artasya (Global Health Science Group, 2020)
The COVID-19 pandemic has been declared a Public Health Emergency of International Concern (PHEIC) because it is troubling the world due to the high morbidity and mortality rates of people around the world. COVID-19 affects all citizens of the world regardless of age, race, and gender. People who have comorbid susceptibility to infection. Covid-19 patients with comorbid diabetes are at high risk for ARDS and multi-organ failure, which are the main causes of death. This literature review aims to provide information on the management of COVID-19 patients with diabetes. The method used is literature reviews from books, international journals, and websites. Literature sources were searched through the NCBI and Google Scholar databases with the keywords COVID-19, SARS-Cov-2, diabetes mellitus, management of COVID-19 with diabetes, management of COVID-19, management of diabetes. The literature obtained totaled 19 articles from 2017 to 2020. The results of the literature review show that diabetic patients with COVID-19 must stick to the medication regimen that has been prescribed, control glucose levels regularly, carry out screening, and live a healthy lifestyle so that therapeutic goals can be achieved. A treatment strategy that focuses on anti-inflammatory as a treatment for COVID-19 and keeps the host's immune response in balance is the best treatment in eliminating COVID-19. Also, patients need to stick to recommended drugs and control their blood glucose levels regularly during this pandemic.